Highly Efficient and Reproducible Nonfullerene Solar Cells from Hydrocarbon Solvents - James Durrant (ACS Energy Letters, 2017)
With chlorinated solvents unlikely to be permitted for use in solution-processed organic solar cells in industry, there must be a focus on developing nonchlorinated solvent systems. Here we report high-efficiency devices utilizing a low-bandgap donor polymer (PffBT4T-2DT) and a nonfullerene acceptor (EH-IDTBR) from hydrocarbon solvents and without using additives. When mesitylene was used as the solvent, rather than chlorobenzene, an improved power conversion efficiency (11.1%) was achieved without the need for pre- or post-treatments. Despite altering the processing conditions to environmentally friendly solvents and room-temperature coating, grazing incident X-ray measurements confirmed that active layers processed from hydrocarbon solvents retained the robust nanomorphology obtained with hot-processed chlorinated solvents. The main advantages of hydrocarbon solvent-processed devices, besides the improved efficiencies, were the reproducibility and storage lifetime of devices. Mesitylene devices showed better reproducibility and shelf life up to 4000 h with PCE dropping by only 8% of its initial value.